P142 Reliability of MEP when using the 1 mV MEP standard to set TMS intensity. Issue 3 (March 2017) - van de Ruit, M.; Grey, M.
Abstract : The inherent variability of motor evoked potential (MEP) recordings is an important consideration when drawing conclusions from studies in which transcranial magnetic stimulation (TMS) is used to assess central nervous system plasticity. Single-pulse TMS assessments have been made at various points on the stimulus intensity – MEP response curve, and MEP variability is dependent on the where one stimulates on this curve. Whilst many studies use the traditional approach of applying stimulation at 120% of the resting motor threshold, another technique that is becoming increasingly common is to set the stimulation intensity to evoke a 1 mV peak-to-peak amplitude MEP. The aim of the present study was to investigate the reliability of single-pulse MEPs elicited at the stimulation intensity set which produce a 1 mV peak-to-peak amplitude response. 52 participants were recruited to the study. MEPs were recorded from the First Dorsal Interosseous (FDI) muscle of the right hand in response to magnetic stimuli delivered over the hand area of the motor cortex. Stimulation intensity was set to evoke an MEP with a 1 mV peak-to-peak amplitude when the muscle was at rest. MEPs were recorded in 8 sets of 30 stimuli with an inter-stimulus interval of 4 s, with 2-min breaks between sets. Coil position and orientation was held constant with frameless stererotaxy. Reliability was assessed using Bland–Altman plots to compare the mean MEP recorded from sets 2–8 with that of the first set. This analysis revealed a consistent deviation from MEPs in the first set with a tendency for MEP amplitude to increase (rmANOVA, p < 0.001). Repeated measures exceeded those at baseline by an average of 0.37 ± 0.06 m. A two-step cluster analysis revealed a significant increase in MEP amplitude in 25% of the participants investigated. We have demonstrated that stimulation delivered with an intensity to produce 1 mV MEPs results in highly variable MEPs with a tendency for the MEPs to increase. Given the intensity to induce 1 mV MEPs differs relative to threshold for every participant this might inflate variability. This result highlights the importance MEP variability and re-emphasises the importance of taking care in concluding changes in MEP amplitude are indeed the result of the intervention as opposed to natural variation of participant attention over time.